Hukuman Rajam Terhadap Pelaku Zina Muhsan (Perspektif Hak Asasi Manusia dan Siyasah Syar’iyah) - Andi Mardika (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2023)
The main problem in this study is how to carry out stoning punishment against adulterers muhsan by taking into account the principles of Human Rights (HAM), as well as examining the problem of stoning regulation as a punishment, seeing it in the view of Human Rights and Islamic Criminal Law. This research is qualitative and based on philosophical theory and phenomenology, which is a theory oriented to be able to get an explanation of the reality that appears. The results of this study indicate that the implementation of stoning punishment against adulterers muhsan is seen as an inhumane punishment based on international regulations such as the Universal Declaration of Human Rights and others. In the perspective of Siyasah Shar'iyah, the imposition of stoning punishment on the perpetrators of adultery muhsan can provide benefits in maintaining honor and offspring. In this case the implementation of stoning punishment can be categorized as part of siyasah shar'iyah with consideration of hifzu al-nasl (preserving offspring) in society.